ECONOMIC CONSTITUTION OF 1993 AND ECONOMIC PERFORMANCE IN PERU - Rodríguez Cairo, Vladimir (2012)
An Economic Constitution characterized by clear rules on economic matters in the constitution of a country for a certain period of its history. However, an important aspect that complements these set of rules and constitutional economic controls the mechanisms, which should exist to fulfill them. Indeed, the regulation of the economics in a constitution is not a practice that has always existed in the legal systems of the world. The German constitution of the Weimar Republic in 1919 is considered by many as the pioneer and is the basis of economic constitutionalism as it established of the basic law of economic activity. For others, the Constitution of 1215 is the first set of economic rules because it placed limitation of the taxing powers of the monarch. Currently, there is a growing consensus on the importance of the Economic Constitution and its institutional framework that contributes positively to the economic performance of a country. In this regard, the following is a historical perspective of the major doctrines, a history of economic constitution (theoretical as well as the content), and a brief analysis of the main rules of the economic game regulated in the current Constitution of 1993, analyzed within its historical context.